Proceso de atención de enfermería en hemorragia posparto en mujeres de Etnia Shuar, según el modelo de Madeleine Leininger, Hospital general de Macas 2021 - Vimos Asitimbay, Mónica Carolina (2021)
Postpartum hemorrhage is one of the main causes of obstetric morbidity and mortality in the world, and in Ecuador, it represents the second cause of death in pregnant women. The nursing professional is the one who provides care to the mother-child dyad during labor and postpartum, whether it is normal or with any complications that may arise. It is essential for the nursing staff to make an incursion into cultural care through Madeleine Leininger's model, in women of Shuar ethnicity, respecting the beliefs and concepts about health; In view of this situation, the idea arises to carry out the present research work to apply the Nursing Care Process in postpartum hemorrhages that are attended at the General Hospital of Macas, whose study approach used is quantitative, with descriptive and transversal bases, having as object of study 11 patients admitted with postpartum hemorrhage and thus recognize the sociodemographic characteristics, needs and culture of Shuar ethnic women to establish the Nursing Care Process. KEY WORDS: postpartum hemorrhage, cultural care, Nursing Care Process, Madeleine Leininger.